1984
DOI: 10.1093/ajcn/40.3.496
|View full text |Cite
|
Sign up to set email alerts
|

Maternal zinc, iron, folic acid, and protein nutriture and outcome of human pregnancy

Abstract: Four hundred fifty women were observed during pregnancy and postpartum. Forty-three variables including 12 laboratory indices of maternal nutrient status were assessed. Of the variance in fetal weight and head circumference 9.9 and 8.1%, respectively, were predictable by polynomial stepwise regression of laboratory indices of maternal nutriture. Maternal plasma zinc levels were inversely correlated with fetal weight. The occurrence of pregnancy complications in the highest and lowest quartiles of maternal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(36 citation statements)
references
References 20 publications
0
32
1
3
Order By: Relevance
“…Though iron (Simmer et al, 1987) and folates (Mukherjee et al, 1984) have an inhibitory effect on zinc absorption, there were no signi®cant differences in the intake of these nutrients between L and H subjects (Table 2).…”
Section: Resultsmentioning
confidence: 94%
“…Though iron (Simmer et al, 1987) and folates (Mukherjee et al, 1984) have an inhibitory effect on zinc absorption, there were no signi®cant differences in the intake of these nutrients between L and H subjects (Table 2).…”
Section: Resultsmentioning
confidence: 94%
“…The intakes of a number of nutrients which have been associated with birthweight, such as iron, magnesium, zinc and thiamin (Mukherjee et al, 1984;Doyle et al, 1990;Haste et al, 1991) were found to be lower among women with more ®nancial dif®culties. However, there was no signi®cant association between dif®culty in affording food and mean birthweight.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, it was reported that folate and zinc had a mutual inhibitory effect at the site of intestinal transport or absorption (Ghishan et al 1986). It was also reported that women with the highest quartile folate and the lowest quartile zinc were vulnerable to fetomaternal complications (Mukherjee et al 1984). Recently, it was demonstrated that high-dose folic acid supplements were associated with adverse effects on fetal mouse development (Mikael et al 2013).…”
Section: Possible Clinical Consequencesmentioning
confidence: 99%